A new genus of angraecoid orchids (Orchidaceae: Angraecinae) with highly distinctive pollinaria morphology, including three new species from tropical West and Central Africa - Descourvières, Pascal; Farminhão, João N. M.; Droissart, Vincent; Dubuisson, Jean-Yves; Simo-Droissart, Murielle; Stévart, Tariq (Phytotaxa, 2018)
A recent large phylogenetic tree for the angraecoid orchids has shown that the Afrotropical genus Diaphananthe is polyphyletic with a small group of four species sister to Aerangis and Eurychone. These species have diagnostic morphological features different from any other angraecoids, notably an erose to fringed surface of the stipes and a calceiform viscidium. Diaphananthe quintasii, which has been regarded as conspecific with D. rohrii, is reinstated as a valid species and lectotypified, and Diaphananthe alfredii and Rhipidoglossum magnicalcar are put in synonymy under D. quintasii. To accommodate this group of species, along with three new taxa from West and Central Africa, a new genus named Kylicanthe is here described. Four new combinations are thus proposed, and K. bueae is chosen as the type species of the new genus and neotypified. Additionally, K. arcuata, K. cornuata, and K. perezverae are described as new species. An identification key for Kylicanthe and allied genera is presented, as well as one for the seven species in the genus. Notes on ecology and distribution in addition to a preliminary assessment of conservation status following the IUCN Red List are also provided.